Differences in Gene Expression Profiles of Seven Target Proteins in Third-Stage Larvae of Anisakis simplex (Sensu Stricto) by Sites of Infection in Blue Whiting (Micromesistius poutassou) - Palomba, Marialetizia (Genes (Basel), 2020)
The third-stage larvae of the parasitic nematode genus Anisakis tend to encapsulate in different tissues including the musculature of fish. Host tissue penetration and degradation involve both mechanic processes and the production of proteins encoded by an array of genes. Investigating larval gene profiles during the fish infection has relevance in understanding biological traits in the parasite’s adaptive ability to cope with the fish hosts’ defense responses. The present study aimed to investigate the gene expression levels of some proteins in L3 of A. simplex (s.s.) infecting different tissues of blue whiting Micromesistius poutassou, a common fish host of the parasite in the NE Atlantic. The following genes encoding for Anisakis spp. proteins were studied: Kunitz-type trypsin inhibitor (TI), hemoglobin (hb), glycoprotein (GP), trehalase (treh), zinc metallopeptidase 13 (nas 13), ubiquitin-protein ligase (hyd) and sideroflexin 2 (sfxn 2). Significant differences in gene transcripts (by quantitative real-time PCR, qPCR) were observed in larvae located in various tissues of the fish host, with respect to the control. ANOVA analysis showed that relative gene expression levels of the seven target genes in the larvae are linked to the infection site in the fish host. Genes encoding some of the target proteins seem to be involved in the host tissue migration and survival of the parasite in the hostile target tissues of the fish host.